CONCEPTUALISATION OF CULTURE PHENOMENA BY PRE-SERVICE TEACHERS OF FOREIGN LANGUAGES - Mazlaveckiene, Gerda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Cultural awareness has become the centre of modern language education that reflects a greater understanding of the inseparability of language and culture, as well as the need to train students for intercultural communication in the globalised world. Realising it or not, language teachers cannot avoid conveying impressions of another culture: language cannot be separated from the culture in which it is embeddedṪherefore, while training a future teacher of a foreign language it is essential to develop his/her cultural awareness, i.e. the knowledge and understanding of the conventions, customs and beliefs of another culture, as well as abilities to interpret, relate and provide critical judgement of one’s native and foreign cultures. Hence, the current article focuses on the conceptualisation of culture phenomena of pre-service teachers of foreign languages. It presents the results of a questionnaire survey conducted at five universities of Lithuania in 2014. The research sample involved 504 pre-service teachers of foreign languages (English, German, French, Polish and Russian), who completed a questionnaire survey consisting of both closed-ended and open-ended questions. The future teachers’ conceptualisation of culture was analysed as twofold: perception and awareness of culture forms of the countries of the native and target languages, as well as their involvement in cultural activity.